Ways to Improve the Financial Viability of the Regions in the Context of the Reform of Fiscal Decentralization Policy in Ukraine (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article deals with the problems of forming the financial base of Ukrainian regions, which have negative impact on the overall socio-economic development of the country. The basic methods and tools address these problems, which are aimed at creating financially capable and independent communities. The authors argued that the process depends primarily on tax revenues to local budgets. Taking into account the difficult political and economic situation there is offered to make free economic zone in the Donbass, which will attract foreign investment in this region and ensure its reconstruction.
Keywords: fiscal decentralization, financial capacity, local communities, local budgets, fiscal policy, Donbas, Ukraine, Spain